PENGARUH KAPASITAS INDIVIDU, KOMITMEN ORGANISASI, DAN LOCUS OF CONTROL TERHADAP BUDGETARY SLACK - Dwi Kriswantini; Annisa Ode (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
This study discusses the effect of individual capacity, organizational commitment and locus of control on budgetary slack to provide evidence of whether individual, organizational commitment and locus of control influence on budgetary slack. This study is a type of survey study by distributing questionnaires to financial managers and finance staff to financial managers and financial staff to State-Owned Enterprises and Regional-Owned Enterprises in Ambon City. Questionnaires were distributed to 80 respondent questionnaires. The results of this study provide evidence that individual capacity has no effect on budgetary slack and is not significant, organizational commitment has an effect on budgetary slack and locus of control has no effect on budgetary slack but significant.